(untitled) (Hakim: Jurnal Ilmu Hukum dan Sosial, 2026)
Barriers that inhibit access to justice remain in existence, thus restricting the capacity of vulnerable groups to interact with the judicial process. The main objective of the current study is to examine the effects of structural barriers on legal processes, legal accessibility, and wider societal outcomes. Further, using an instrumental case study design, a total of 36 respondents with experiences of civil or minor crimes in five areas of Indonesia were chosen by maximum variation sampling. Thematic analysis supported by NVivo 14 was used to analyze data obtained through semi-structured interviews, participant observation, and document analysis. It also analyzed the relationships among economic, institutional, procedural, social, as well as technological barriers. All of the above were considered. It is evident from the results that structural barriers are present in different ways, occurring as a result of cumulative events rather than individual ones throughout the legal system. Procedural, institutional, social and technological barriers were reinforced by economic barriers as the initial trigger, leading to a cycle that disproportionately prevented certain groups from accessing meaningful justice. This work contributes an integrative analytical framework to the literature on access to justice by explaining the causal interaction among structural barriers. The outcomes highlight the need for multidimensional, context-sensitive legal reform to alleviate structural inequalities and promote equitable access to justice.